Bamboo‐Like Nitrogen‐Doped Carbon Nanotube Forests as Durable Metal‐Free Catalysts for Self‐Powered Flexible Li–CO2 Batteries. Issue 39 (9th August 2019) - Li, Xuelian; Zhou, Jingwen; Zhang, Junxiang; Li, Matthew; Bi, Xuanxuan; Liu, Tongchao; He, Tao; Cheng, Jianli; Zhang, Fan; Li, Yongpeng; Mu, Xiaowei; Lu, Jun; et al.
Abstract: The Li–CO2 battery is a promising energy storage device for wearable electronics due to its long discharge plateau, high energy density, and environmental friendliness. However, its utilization is largely hindered by poor cyclability and mechanical rigidity due to the lack of a flexible and durable catalyst electrode. Herein, flexible fiber‐shaped Li–CO2 batteries with ultralong cycle‐life, high rate capability, and large specific capacity are fabricated, employing bamboo‐like N‐doped carbon nanotube fiber (B‐NCNT) as flexible, durable metal‐free catalysts for both CO2 reduction and evolution reactions. Benefiting from high N‐doping with abundant pyridinic groups, rich defects, and active sites of the periodic bamboo‐like nodes, the fabricated Li–CO2 battery shows outstanding electrochemical performance with high full‐discharge capacity of 23 328 mAh g −1, high rate capability with a low potential gap up to 1.96 V at a current density of 1000 mA g −1, stability over 360 cycles, and good flexibility. Meanwhile, the bifunctional B‐NCNT is used as the counter electrode for a fiber‐shaped dye‐sensitized solar cell to fabricate a self‐powered fiber‐shaped Li–CO2 battery with overall photochemical–electric energy conversion efficiency of up to 4.6%. Along with a stable voltage output, this design demonstrates great adaptability and application potentiality in wearable electronics with a breath monitor as an example. Abstract : A self‐powered fiber‐shaped Li–CO2 battery with overall photochemical–electric energy conversion efficiency of up to 4.6% is fabricated using bifunctional bamboo‐like N‐doped carbon nanotube fiber as the cathode for the Li–CO2 battery and as the counter electrode for the dye‐sensitized solar cells simultaneously. The fiber‐shaped Li–CO2 batteries show high specific capacity, long cycle life, and high flexibility.